Short-term warming supports mineral-associated carbon accrual in abandoned croplands - Zhenrui Zhang; Hui Gao; Xiaoxia Gao; Shurui Huang; Shuli Niu; Emanuele Lugato; Xinghui Xia (Nature Communications)
Abstract Effective soil organic carbon (SOC) management can mitigate the impact of climate warming. However, the response of different SOC fractions to warming in abandoned croplands remains unclear. Here, categorizing SOC into particulate and mineral-associated organic carbon (POC and MAOC) with physical fractionation, we investigate the responses of POC and MAOC content and temperature sensitivity (Q10) to warming through a 3-year in situ warming experiment (+1.6 °C) in abandoned croplands across 12 sites in China (latitude: 22.33–46.58°N). Our results indicate that POC content remains unchanged while MAOC content significantly increases under warming. POC and MAOC content changes are mainly influenced by root biomass and microbial necromass carbon changes, respectively. The Q10 of MAOC is significantly lower than that of POC regardless of the warming or control treatment, suggesting that MAOC represents the most persistent and least vulnerable carbon fraction within SOC. Collectively, the sequestration of stable soil carbon can be enhanced in abandoned croplands under short-term warming.